Application of Turbulent Reacting Flow Analysis in Gas Turbine Combustor Development - NISHIDA, Hiroyuki; MANDAI, Shigemi (JSME International Journal Series B Fluids and Thermal Engineering, 2004)
Developing a low NOX gas turbine combustor usually requires many experiments on flow and combustion. Computational prediction technology in the field of combustion has progressed with advances in computer technology and turbulent combustion models. This report covers applications of CFD for the development of the gas turbine combustor and some discrepancies between CFD and test results as well as improved methods for resolving such discrepancies.